The Role of Corporate Governance and Firm Characteristics in Earnings Management - Josephine Azalia Conselo; Deasy Ariyanti Rahayuningsih (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this study was to obtain empirical evidence regarding the effect of corporate governance and company characteristics on earnings management. Corporate governance consists of: managerial ownership, institutional ownership, board of directors and audit quality. Company characteristics consist of: firm size, profitability, leverage and firm age. The sample in this study was 116 non-financial companies listed on the IDX from 2019-2021. A total of 348 data were selected using purposive sampling and the hypothesis was tested using multiple regression. The results of this study indicated that two variables namely profitability which has a positive effect and audit quality has a negative effect. The remaining six variables have no effect on earnings management because the variables managerial ownership and institutional ownership are less effective in reducing earnings management in companies. The number of boards doesn’t affect the function and ability of the board of directors, the existence of public attention, the company's obligation to pay debts and the age of the company which does not guarantee a company do earnings management makes company characteristics such as the size of the board of directors, firm size, leverage and company age cannot be used as an indication a company performs earnings management.